Evidence of pollen features and peroxidase isozymes in their morphological complexity of ten local cultivars of sweet potato from Indonesia - Suranto Suranto; DWI WAHYUNI; EDY PURWANTO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Suranto, Wahyuni D, Edy Purwanto E. 2019. Evidence of pollen features and peroxidase isozymes in their morphological complexity of ten local cultivars of sweet potato from Indonesia. Biodiversitas 20: 2511-2518. Sweet potato (Ipomoea batatas Lam) has been recorded to have many cultivars and variations in the morphological characters not only for the leaves but also for the tubers. Sweet potatoes had economically significant role, especially as an additional food due to its high content of carbohydrate and other nutrient values. In order to test whether the morphological variation in this species was also expressed at the micro character; such as pollen morphology and enzyme activity, ten sweet potato cultivars were used in this study. The morphological characters such as shape and structure of the pollen features were examined using Scanning Electron Microscopy (SEM). Accordingly, Polyacrylamide Gel Electrophoresis (PAGE) was used to look-at the banding pattern of peroxidase isozymes. Morphological characters of leaves, flowers, and tuber were observed qualitatively both for the typical shape and colors. More detail of flower shapes was drown manually especially their petal edges. The results showed that there was variation among the ten sweet potato cultivars confirmed not only on their morphological characters but also the isozyme banding patterns of ten cultivars tested. At least, two cultivar Antin 3 and Papua Solossa had uniques characters especially the purple stem and yellow tuber and dark skin on the tuber, respectively. In addition, the structural analysis of pollen showed that Beta 1 cultivar has very large pollen; 116,50 ?m (axis polar) and the contour surface of exine pollen was concave with the aperture shape and ornamentation were prolate spheroidal and echinate respectively. This unique character was also shown by its peroxidase isozyme bands. Eleven bands of leaf and 13 bands of stem samples were detected respectively. The typical Rf values of 0.31, 0.48 and 0.41 were detected for the leaf, while for stem samples were 0.14, 0.20 and 0.26. The Beta 1 cultivar showed very thick bands in between Rf values of 0.13 and 0.26. Meanwhile, the unique band pattern of Papua Salosa was the absence of band at 0.38.